2022
DOI: 10.3390/v14020389
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis and Synthesis of Nafamostat Derivatives and Evaluation of Their Anti-SARS-CoV-2 Activity

Abstract: Inhibition of transmembrane serine protease 2 (TMPRSS2) is expected to block the spike protein-mediated fusion of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Nafamostat, a potent TMPRSS2 inhibitor as well as a candidate for anti-SARS-CoV-2 drug, possesses the same acyl substructure as camostat, but is known to have a greater antiviral effect. A unique aspect of the molecular binding of nafamostat has been recently reported to be the formation of a covalent bond between its acyl substructure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 37 publications
(49 reference statements)
0
17
0
Order By: Relevance
“…The ratios were calculated to be 7.59×10 4 , 3.04×10, and 1.65×10 −12 for nafamostat, camostat, and compound 1, respectively, indicating that the acyl intermediate is more likely to be formed with nafamostat and camostat, and less likely to be formed with compound 1. These thermodynamic analyses successfully reproduced a trend in the inhibitory activities of the three compounds which was obtained from in vitro studies 20 .…”
mentioning
confidence: 52%
See 4 more Smart Citations
“…The ratios were calculated to be 7.59×10 4 , 3.04×10, and 1.65×10 −12 for nafamostat, camostat, and compound 1, respectively, indicating that the acyl intermediate is more likely to be formed with nafamostat and camostat, and less likely to be formed with compound 1. These thermodynamic analyses successfully reproduced a trend in the inhibitory activities of the three compounds which was obtained from in vitro studies 20 .…”
mentioning
confidence: 52%
“…The calculations indicated the nafamostat derivative where the ester bond of nafamostat was replaced with an amide bond (compound 1) as having the highest binding affinity. Based on this result, we expected compound 1 exhibiting the strongest inhibitory activity 20 ; however, in vitro assays using SARS-CoV-2-infected cells demonstrated that compound 1 had the weakest inhibitory activity 20 .…”
mentioning
confidence: 91%
See 3 more Smart Citations